2015
DOI: 10.12659/msmbr.895563
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Reprogrammed In Vitro Towards the M1 Phenotype and Activated with LPS Extend Lifespan of Mice with Ehrlich Ascites Carcinoma

Abstract: BackgroundThe majority of tumors trigger macrophage reprogramming from an anti-tumor M1 phenotype towards a pro-tumor M2 phenotype. The M2 phenotype promotes tumor growth. We hypothesized that increasing the number of M1 macrophages in a tumor would limit carcinogenesis and extend the lifespan of the tumor host. The aim of this study was to verify this hypothesis in Ehrlich ascites carcinoma (EAC). The objectives were to evaluate effects of 1) EAC on a macrophage phenotype and NO-producing macrophage activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 56 publications
(63 reference statements)
2
22
1
4
Order By: Relevance
“…Unlike stably differentiated cells, M1 and M2 macrophages can switch phenotypes [23][24][25]. Thus, reprogramming M2 TAMs towards the immunogenic M1 phenotype in vivo to block tumor progression could be a promising strategy for the treatment of cancers.…”
mentioning
confidence: 99%
“…Unlike stably differentiated cells, M1 and M2 macrophages can switch phenotypes [23][24][25]. Thus, reprogramming M2 TAMs towards the immunogenic M1 phenotype in vivo to block tumor progression could be a promising strategy for the treatment of cancers.…”
mentioning
confidence: 99%
“…For instance, previous study demonstrated LPS‐induced osteoclastic multinucleated cell formation through the SAPK/JNK pathway (Islam et al, ). Another study showed LPS as one of key stimuli that could stimulate macrophages M1 polarization by the effect of AP‐1 (Al Faraj et al, ; Kalish et al, ). Thus, we speculated that the two transcription factors c‐Fos and Nfatc1 are involved in the LPS‐induced osteoclastogenesis in RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage recruitment, polarization, and function are important for the proper resolution of many bacterial infections. In a typical response, circulating monocytes are recruited to the site of infection upon signaling by damage-associated and pathogen-associated molecular patterns (DAMPs and PAMPs), and proinflammatory cytokines such as IL-6, IFNγ, and TNFα; these arriving monocytes initially differentiate, or polarize, toward proinflammatory (M1) macrophages (17)(18)(19)(20)(21)(22)(23)(24)(25). These M1 cells further secrete proinflammatory cytokines and chemokines, exert phagocytic activity, and induce neutrophil apoptosis (25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%